THE EFFECT OF ENTREPRENEURSHIP EDUCATION, PARENTAL SUPPORT, AND INTERNAL LOCUS OF CONTROL ON SELF-EFFICACY MODERATING INTEREST IN ENTREPRENEURSHIP - Muhammad Vicky Zulfikar; Ery Tri Djatmika Rudijanto Wahju Wardhana; Wening Patmi Rahayu (Yayasan Education and Social Center, 2022)
Interest in entrepreneurship is an act of individual desire to do business. Interest in entrepreneurship arises because of the urge to prove what is obtained from knowledge and information. The desire to be involved in business activities is also a factor in a person's interest in entrepreneurship. This study examines the effect of entrepreneurship education, parental support, internal locus of control, and self-efficacy on interest in entrepreneurship. The sample in this study was 148 students from UMM, Unisma, and Unikama. The data analysis technique used is a descriptive data analysis technique, Partial Least Square (PLS) method using SmartPLS version 3 software, and hierarchical structural equation modeling. This study found a significant effect of entrepreneurship education, parental support, and internal locus of control on interest in entrepreneurship. Self-efficacy has a positive influence in moderating entrepreneurship education, parental consent, and internal locus of control on entrepreneurial interest